Bloomsbury Good Reading Guide - Rennison, Nick (Bloomsbury Publishing Plc, 2008)
Deciding what to read next when you've just finished an unputdownable novel can be a daunting task. The Bloomsbury Good Reading Guide features hundreds of authors and thousands of titles, with navigation features to lead you on a rich journey through some the best literature to grace our shelves.